Highly Active Ice‐Nucleating Particles at the Summer North Pole. Issue 6 (17th March 2022) - Porter, Grace C. E.; Adams, Michael P.; Brooks, Ian M.; Ickes, Luisa; Karlsson, Linn; Leck, Caroline; Salter, Matthew E.; Schmale, Julia; Siegel, Karolina; Sikora, Sebastien N. F.; Tarn, Mark D.; Vüllers, Jutta; et al.
Abstract: The amount of ice versus supercooled water in clouds is important for their radiative properties and role in climate feedbacks. Hence, knowledge of the concentration of ice‐nucleating particles (INPs) is needed. Generally, the concentrations of INPs are found to be very low in remote marine locations allowing cloud water to persist in a supercooled state. We had expected the concentrations of INPs at the North Pole to be very low given the distance from open ocean and terrestrial sources coupled with effective wet scavenging processes. Here we show that during summer 2018 (August and September) high concentrations of biological INPs (active at >−20°C) were sporadically present at the North Pole. In fact, INP concentrations were sometimes as high as those recorded at mid‐latitude locations strongly impacted by highly active biological INPs, in strong contrast to the Southern Ocean. Furthermore, using a balloon borne sampler we demonstrated that INP concentrations were often different at the surface versus higher in the boundary layer where clouds form. Back trajectory analysis suggests strong sources of INPs near the Russian coast, possibly associated with wind‐driven sea spray production, whereas the pack ice, open leads, and the marginal ice zone were not sources of highly active INPs. These findings suggest that primary ice production, and therefore Arctic climate, is sensitive to transport from locations such as the Russian coast that are already experiencing marked climate change. Plain Language Summary: Clouds play a critical role in Earth's climate, both reflecting incoming sunlight and trapping outgoing infrared radiation. Hence, even small errors in the representation of clouds in climate models can lead to uncertainty in predictions of, for example, sea ice extent. In the Arctic, liquid clouds often exist below 0°C and cloud water droplets can exist in a supercooled liquid state. In the absence of special particles that can trigger ice formation in droplets, ice‐nucleating particles (INPs), supercooled water droplets can cool well below −35°C before spontaneously freezing. The presence of INPs can reduce the lifetime of a cloud and the amount of supercooled water in clouds, making them less reflective. Based on our knowledge of INPs in other remote oceans, we expected very low INP concentrations in the central Arctic. However, we found very high concentrations of biological INPs in the summertime North Pole. Furthermore, these INPs come from the seas off the coast of Russia, a region already experiencing strong climate change. It is possible that these sources may become even more important as the Arctic becomes increasingly ice‐free, causing changes in Arctic clouds and further changes in climate. Key Points: The concentration of ice‐nucleating particles at the North Pole in summer 2018 was amongst the highest anywhere in the world Biological ice‐nucleating particles were derived from the Russian seas and perhaps associated with wind‐driven sea spray The concentration of ice‐nucleating particles at the surface was often different to that higher in the boundary layer where clouds form